Psychological Effects of Abortion on Women: A Review of the Literature - FINE-DAVIS, MARGRET (Crisis Pregnancy Agency, 2007)
The psychological effects of abortion have been the subject of scientific investigation, as well as public debate internationally, for several decades and have generated a great deal of discussion, as well as some controversy. Given the importance of this matter for women and the significant public health implications resulting from it, it is an important issue upon which to focus attention from a health policy point of view
PUBLISHED
Keywords: psychological effects of abortion; Abortion